2021
DOI: 10.3390/mi12111356
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Field-Assisted Ultraviolet Nanosecond Pulse Laser Processing of Polyethylene Terephthalate (PET) Film

Abstract: Understanding the mechanism of and how to improve the laser processing of polymer films have been important issues since the advent of the procedure. Due to the important role of a photothermal mechanism in the laser ablation of polymer films, especially in transparent polymer films, it is both important and effective to adjust the evolution of heat and temperature in time and space during laser processing by simply adjusting the ambient environment so as to improve and understand the mechanism of this procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…There are six papers published in this Special Issue focusing on pulsed laser machining. From metallic [1,2], inorganic [3] and polymeric [4,5] materials to biomass materials [6], from surface texture microstructures [1] and grain microstructures [2] to various types of functional contour structures [4,5], from the laser processing of metallic materials [1,2] and inorganic nonmetallic materials [3] to polymeric materials [4,5], from flexible electronics [4,5] and new energy batteries [1] to biomedicine [6], the articles in this Special Issue explore the specific applications of pulsed lasers in various fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are six papers published in this Special Issue focusing on pulsed laser machining. From metallic [1,2], inorganic [3] and polymeric [4,5] materials to biomass materials [6], from surface texture microstructures [1] and grain microstructures [2] to various types of functional contour structures [4,5], from the laser processing of metallic materials [1,2] and inorganic nonmetallic materials [3] to polymeric materials [4,5], from flexible electronics [4,5] and new energy batteries [1] to biomedicine [6], the articles in this Special Issue explore the specific applications of pulsed lasers in various fields.…”
mentioning
confidence: 99%
“…In the pulsed laser processing of polymeric materials, Xu et al's [4] studies on the thermoplastic PET film and on temperature field-assisted ultraviolet nanosecond (UV-ns) pulse laser processing of polyethylene terephthalate (PET) film were performed to investigate the photothermal ablation mechanism and the effects of temperature on laser processing. The results showed that the UV-ns laser processing of PET film was dominated by the photothermal process in which PET polymer chains decomposed, melted, recomposed and reacted with the ambient gases.…”
mentioning
confidence: 99%